2009
DOI: 10.1093/heapol/czn052
|View full text |Cite
|
Sign up to set email alerts
|

Paying for hospital-based care of Kala-azar in Nepal: assessing catastrophic, impoverishment and economic consequences

Abstract: Households obtaining health care services in developing countries incur substantial costs, despite services generally being provided free of charge by public health institutions. This constitutes an economic burden on low-income households, and contributes to deepening their level of poverty. In addition to the economic burden of obtaining health care, the method of financing these payments has implications for the distribution of household assets. This effect on resource-poor households is amplified since the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 21 publications
6
75
0
1
Order By: Relevance
“…19 In the same line, other study showed that 34% of the hospitalised patients had impoverished because of medical costs. 20 Moreover, the households with higher inpatient expenses were more likely to borrow money and deplete their assets. 21 This negative impact of health expenditures on households that can lead to impoverishment has long been ignored in the health policy agenda.…”
Section: Discussionmentioning
confidence: 99%
“…19 In the same line, other study showed that 34% of the hospitalised patients had impoverished because of medical costs. 20 Moreover, the households with higher inpatient expenses were more likely to borrow money and deplete their assets. 21 This negative impact of health expenditures on households that can lead to impoverishment has long been ignored in the health policy agenda.…”
Section: Discussionmentioning
confidence: 99%
“…Households in poorer quintiles are more at risk of suffering catastrophic health expenditure and their impoverishment is more common, which is similar to other studies. 22,23 The capacity to pay of the wealthiest population quintile is around 10 times higher than that of the poorest. Disparities in social, economic and environmental conditions in different regions of China also play a part in the risk of experiencing catastrophic health expenditure.…”
Section: Health-care Needs Utilization and Capacity To Paymentioning
confidence: 99%
“…In fact, it appeared that the households of 172 (75%) of the patients included in the final analysis had had to bear catastrophic health expenditures. Even when more conservative thresholds for catastrophic health expenditure were applied -15% or 25% of annual household income 17,18 many of the households of tuberculosis patients (66% and 48%, respectively) still appeared to have been faced with tuberculosis-related expenditures that were categorized as catastrophic. We therefore conclude that, in rural districts of Burkina Faso, the risk of catastrophic health expenditure associated with tuberculosis is high, even in the context of a "free" package of tuberculosis care.…”
Section: The Cost Of "Free" Tuberculosis Carementioning
confidence: 99%